Evaluation of a Multiplex PCR-Based Reverse Line Blot-Hybridization Assay for Identification of Serotype and Surface Protein Antigens of Streptococcus agalactiae - Zeng, Xianyu (American Society for Microbiology, 2006)
A 33-primer multiplex PCR-based reverse line blot (mPCR/RLB) assay was developed to identify Streptococcus agalactiae serotypes and surface protein antigen genes simultaneously. It was evaluated by using 551 clinical isolates. The mPCR/RLB assay was more sensitive than conventional serotyping, especially for protein antigen typing, but otherwise the results correlated well.